Importance of environmental and hydrospatial monitoring systems – The UK Hydrographic Office Marine Environmental Monitoring Stations Framework - Conway, Becky (The International Hydrographic Review, 2025)
An ever-increasing need for reliable, real-time marine environmental and hydrospatial data has lead to development of a Marine Environmental Monitoring Stations framework by the UK Hydrographic Office. This framework, executed in partnership with OceanWise, involves the installation, operation, and maintenance of monitoring stations across various global locations, whilst emphasizing the importance of local stakeholders engagement. The framework aims to enhance navigational safety, provide critical data for climate change research, and support various government initiatives. OceanWise’s cloud-based data platform enables real-time data visualization as well as access to historical records to support this. This approach not only supports scientific research and maritime safety but also fosters local capacity building and long-term sustainability in data management.